2017
DOI: 10.1186/s12876-017-0629-2
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of gut microbiota in association with cholesterol gallstone formation in mice

Abstract: BackgroundThe gut microbiome exerts extensive roles in metabolism of nutrients, pharmaceuticals, organic chemicals. Little has been known for the role of gut microbiota in regulating cholesterol and bile acids in association with gallstone formation. This study investigated the changes in the composition of gut microbiota in mice fed with lithogenic diet (LD).MethodsAdult male C57BL/6 J mice were fed with either lithogenic diet (1.25% cholesterol and 0.5% cholic acid) or chow diet as control for 56 days. The f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
54
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(55 citation statements)
references
References 45 publications
1
54
0
Order By: Relevance
“…Wang et al [3] showed that gut microbiota at different levels changed with gallstone formation, indicating that gut microbiota dysbiosis plays an important role in the promotion of gallstone formation. Fremont-Rahl et al found that compared to the control group, the incidence rate of cholesterol gallstones in sterile mice fed LD significantly increased.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Wang et al [3] showed that gut microbiota at different levels changed with gallstone formation, indicating that gut microbiota dysbiosis plays an important role in the promotion of gallstone formation. Fremont-Rahl et al found that compared to the control group, the incidence rate of cholesterol gallstones in sterile mice fed LD significantly increased.…”
Section: Discussionmentioning
confidence: 99%
“…Most (90%) gallstones are cholesterol gallstones [2]. The pathogenesis of cholesterol gallstones is still not clear, though studies suggest that gut microbiota dysbiosis plays an important role in their formation [3]. The gut microbiota participates in the metabolism of substances and energy, promotes the development and maturation of the immune system, forms the mucosal barrier, and protects the host from pathogen attacks [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, abnormal BAs pool composition is a proposed determinant for cancer in the proximal colon and rectum and pancreas as well as cholangiocarcinoma, inflammatory bowel disease, and metabolic syndrome . BAs composition influences the balance between bacterial populations in the intestine, such has been observed in mice fed a lithogenic diet and in patients with GSD who show decreased microbial diversity and dysbiosis . Importantly, although cholecystectomy results in a continuous cycling of BAs pool in the enterohepatic circulation; its impact on BAs pool composition is less clear.…”
Section: Potential Roles Of the Gb On Glucose And Lipid Metabolism Anmentioning
confidence: 99%
“…Current studies have shown that changes in gut microbiota are associated with the formation of cholesterol gallstones. Wang et al [3] investigated the faeces of mice with cholesterol gallstones using 16S ribosomal RNA (16s rRNA) gene sequencing and found that in the intestinal tract of mice, the Firmicutes content and the Firmicutes/Bacteroidetes (F/B) ratio decreased, the abundances and diversity of the microbiota also significantly decreased, and a lithogenic diet (LD) reshaped the abundances of gut microbiota at different levels. Keren et al found that in patients with gallstones, the microbial diversity was reduced and the total bile acid concentration in faeces was increased [8].…”
mentioning
confidence: 99%